The Saturne cementless dual‐mobility cup grants satisfactory long‐term survival - Thierry Gaillard; Sonia Ramos‐Pascual; Mo Saffarini; Jean‐Pierre Piton (Journal of Experimental Orthopaedics, 2022)
Abstract Purpose To report long‐term survival and clinical outcomes of primary total hip arthroplasty (THA) using a Saturne cementless dual‐mobility (DM) cup, and investigate whether patient demographics or surgical parameters affect clinical scores. Methods A consecutive series of primary THAs implanted with Saturne cementless DM cups between 01/09/2009–31/12/ 2011 was retrospectively assessed. Patients were postoperatively evaluated using modified Harris hip score (mHHS) and forgotten joint score (FJS). Complications, reoperations, and revisions were noted. Regression analyses were performed to determine associations of postoperative mHHS with preoperative and intraoperative variables. Ten‐year Kaplan–Meier survival was calculated. Results Of 308 patients (308 hips), 111 (36%) had died with their original cups in place, 29 (9%) were lost‐to‐follow‐up, and 5 (2%) required cup revision, leaving a final cohort of 163 (53%) with their original cup in place at a follow‐up of ≥ 10 years. Ten‐year survival was 98% considering cup revision for any reason as endpoint; 99% considering cup revision for aseptic loosening as endpoint; 96% considering stem revision for any reason as endpoint; and 96% considering any revision as endpoint. The final cohort of 163 patients was assessed at 11 ± 1 years (range, 10–13), mHHS was 85 ± 16 (range, 31–100) and FJS was 84 ± 24 (range, 0–100). Multivariable regression analysis revealed that postoperative mHHS significantly worsened with age (β = ‐0.48, p = 0.007) and BMI (β = ‐0.70, p = 0.008), as well as for 22 mm head sizes (β = ‐6.98, p = 0.046). Conclusions The Saturne DM cup granted satisfactory survival and clinical outcomes at a minimum follow‐up of 10 years, and resulted in no cases of intra‐ or extra‐prosthetic dislocations.